"Was ist Wahrheit anderes als ein Leben für eine Idee?: Kierkegaards Existenzdenken und die Inspiration des Pragmatismus ; gesammelte Aufsätze zur Theologie und Religionsphilosophie - Deuser, Hermann (De Gruyter, 2011)
Since the early 20th century internationally renowned scholars have regularly rediscovered the significance of Søren Kierkegaard for the philosophy of religion and theology. However, only recently have they explored the affinity between the North American philosophy of pragmatism and Kierkegaard's existential thinking.This collection of essays documents a process of adoption and interpretation that over the last thirty years has sought to overcome the traditional way of reading Kierkegaard's works. As the essays reveal, the original pragmatists - especially William James and Charles S. Peirce